Swelling Behavior of Chemically Ion‐Doped Hydrogels - Alveroglu, Esra; Gelir, Ali; Yilmaz, Yasar (Wiley, 2009)
AbstractSummary: Poly(acrylamide‐co‐N,N′‐methylenebisacrylamide) gels were synthesized in the presence of pyranine fluoroprobe (trisodium 8‐hydroxypyrene‐1,3,6‐trisulfonate). Pyranine binds to polymer chains through its OH group via radical addition. Thus, the final gels were doped with the pyranines having SO ions as side groups and Na+ as counter‐ions. The swelling behavior of gels prepared with varying amounts of pyranine and monomer concentrations were studied. The swelling ratio of the synthesized gels did not exceed 35 except the 2 M gel containing 10−2 M pyranine which are the concentrations for the abnormal swelling behavior. At this particular concentration of monomer (acrylamide) and pyranine, the mass ratio m/m0, the mass of the swollen gel to the mass of the dried gel, reaches about 1300; a stepwise behavior was observed in the swelling kinetics. The swelling kinetics of polyacrylamide gels containing unbound (free) pyranine were compared with the swelling behavior of the gels containing chemically bound pyranine.